PERANCANGAN VIDEO ANIMASI LIRIK LAGU SAYU - Puspita, Ako Naomi Ratna; Haryatno, Yulius Rudi (Jurnal Industri Kreatif dan Inovatif, 2025)
Lyric videos play an important role in the music industry, combining visual, audio and text elements to convey the message of a song. This research aims to animate the lyric video for the song "Sayu" by improving visual quality and motion graphic elements. The goal is to strengthen the audience's understanding of the meaning of the lyrics and amaze the audience with a more immersive visual experience. The creation of this work uses qualitative descriptive approach to interpretation and visualization of text. This research is motivated by awareness of the issue of preserving wild animals, especially orangutans, which are threatened with extinction. The song "Sayu" contains a strong social message about preserving wild animals, and through animated lyric videos, this research seeks to increase public understanding of this issue. In developing content, this research uses the MDLC (Multimedia Development Life Cycle) technique, creative typography, 2D animation elements, and motion graphics to create lyric videos that are more visually attractive. The expected final result is a lyric video that is effective in conveying the lyric's message and supporting public awareness about the conservation of wild animals.